DISTANCE LEARNING FOR A FOREIGN LANGUAGE AT A HIGHER MILITARY INSTITUTIONS IN MODERN CONDITIONS - Golovan , Vyacheslav; Gorlichenko, Andrii; Drozdov , Mykhailo (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article examines the most important aspects of the implementation and development of distance learning of foreign languages ​​for cadets (students, students) in higher military educational institutions in the conditions of a pandemic and external aggression. On the basis of practical experience, the authors come to the conclusion that the introduction of distance education in higher educational institutions is appropriate not only as an effective means of solving force-majeure problems, but is a central perspective for the development of the higher education system of Ukraine for any distant future. Today, remote learning of a foreign language by the military is the most comfortable and affordable means of its fastest mastery and dissemination for the purpose of effective military-professional interaction with the military personnel of NATO countries and the subsequent integration of the Ukrainian Armed Forces with this European defense organization. Interactivity in access to learning content, the ability of the distance education system to provide practically unlimited and, at the same time, clearly structured and media-supported information and educational resources, increased independent cognitive activity of those who study, comfort in use greatly contribute to the achievement of motivation and learning goals.